Cu2O / FeOx-coated CNFs heterojunction nano-enzyme as well as preparation method and application of Cu2O / FeOx-coated CNFs heterojunction nano-enzyme

Cu2O/FeOx p-n heterojunction was prepared by loading Cu2O/FeOx p-n heterojunction on carbon nanofibers, which solved the problems of low catalytic efficiency and insufficient stability of nanoenzymes, and achieved efficient Fenton reaction and pollutants Degradable, recyclable, suitable for food safety.

CN119114075APending Publication Date: 2024-12-13SHAANXI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411007619.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing nanoenzymes have low catalytic efficiency and insufficient stability in Fenton reactions, and are difficult to recover in food sample applications, resulting in secondary contamination problems.

Method used

Cu2O/FeOx p-n heterojunction nanozyme was prepared by loading Cu2O/FeOx p-n heterojunction nanozymes on carbon nanofibers, and the built-in electric field was used to accelerate the reduction of Fe(III), improve catalytic activity, and realize nanozymes through magnetic properties recyclability.

Benefits of technology

It significantly improves the efficiency of Fenton reaction, shows efficient sterilization and pollutant degradation capabilities, has good antibacterial effects and magnetic separation properties, is suitable for food safety and reduces treatment costs and environmental risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114075A_ABST
    Figure CN119114075A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of food safety, and particularly relates to a Cu2O / FeOx-CNFs heterojunction nano-enzyme and a preparation method and application thereof.The preparation method comprises the steps that S1, bacterial cellulose BC is subjected to decoloration and cleaning pretreatment; s2, immersing the pretreated BC into a mixed solution containing Fe (II) and Cu (II), uniformly stirring, and washing to obtain BC-Cu (II) / Fe (II); and S3, carrying out freeze drying, pre-oxidation, carbonization and cooling so as to obtain the Cu2O / FeOx-coated CNFs heterojunction nano-enzyme. The Cu2O / FeOx p-n heterojunction is synthesized in the upper limit domain of the carbon nanofiber, and the obtained heterojunction nano-enzyme can significantly enhance the catalytic efficiency of the traditional Fenton reaction, shows efficient peroxidase-like activity, and has both high stability and strong magnetism; the product has broad-spectrum sterilization and pollutant degradation properties, and can be used in the field of food safety control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food safety and particularly relates to a Cu2O / FeO x @CNFs heterojunction nanozymes and their preparation methods and applications. Background Art

[0002] The Fenton reaction is an effective method for degrading organic pollutants and is widely used in the field of water treatment. The core principle of the Fenton reaction is to use ferrous ions (Fe(II)) as a catalyst to react with hydrogen peroxide (H2O2) under acidic conditions to produce hydroxyl radicals (·OH). These radicals have extremely high reactivity and can degrade microorganisms and organic pollutants in water. The Fenton reaction is favored for its mild reaction conditions, simple equipment requirements and convenient operation, but its efficiency is often limited by the fact that Fe(II) is difficult to quickly reduce back to Fe(II) after being oxidized to ferric ions (Fe(III)) during the reaction, resulting in a slow reduction rate, which leads to low efficiency in the generation of hydroxyl radicals, thereby affecting the rate of the entire reaction. In addition, the iron salts used in traditional Fenton technology are difficult to recover after the reaction, which not only increases the treatment cost, but may also cause secondary pollution problems.

[0003] Nanozymes are a type of nanomaterials that mimic enzyme catalysis. They have good thermal stability, pH stability, and resistance to organic pollution. They can achieve efficient catalysis of substrates by simulating the active sites of biological enzymes. Nanozymes with peroxidase-like activity have Fenton reaction (the catalytic active center is Fe(II)) or Fenton-like reaction activity. However, nanozymes with Fenton reaction activity are still subject to the limitation of Fe(III) reduction rate in application, with low catalytic efficiency and insufficient stability. In addition, nanozymes are difficult to recover in food sample applications, which can easily cause secondary food contamination. Summary of the invention

[0004] In order to solve the problems of low catalytic efficiency and insufficient stability of the existing nanozyme Fenton reaction, the present invention provides a Cu2O / FeO x @CNFs heterojunction nanozymes and their preparation methods and applications.

[0005] The present invention loads Cu2O / FeO on carbon nanofiber x pn heterojunction, preparation of Cu2O / FeO with high stability and strong magnetism x @CNFs heterojunction nanozyme improves the efficiency of Fenton reaction and enhances enzyme catalytic activity; the nanozyme has the ability of broad-spectrum bactericidal and pollutant degradation and can be used in the field of food safety.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A Cu2O / FeO x The preparation method of @CNFs heterojunction nanozyme comprises the following steps:

[0008] S1, decolorizing and washing bacterial cellulose BC to complete pretreatment;

[0009] S2. The pretreated BC is immersed in a mixed solution containing Fe(II) and Cu(II), stirred evenly, and then rinsed to obtain BC-Cu(II) / Fe(II); the mass volume ratio of the BC and the mixed solution is (4mg~6mg):0.5L; the concentration of Fe(II) is 10mmol / L~30mmol / L, and the concentration of Cu(II) is 10mmol / L~25mmol / L.

[0010] S3, the BC-Cu(II) / Fe(II) in step S2 is freeze-dried, pre-oxidized, carbonized, and cooled to obtain Cu2O / FeO x @CNFs heterojunction nanozymes.

[0011] It is further defined that in step S1, the decolorization is carried out in an alkaline environment, the decolorization temperature is 80° C. to 100° C., and the decolorization time is 1.5 h to 3 h; and the washing is carried out with water.

[0012] It is further defined that in step S2, the concentration ratio of Fe(II) to Cu(II) is (1-3):1.

[0013] It is further defined that in step S2, the stirring time is 6 hours to 24 hours.

[0014] It is further defined that in step S3, the pre-oxidation temperature is 150° C. to 200° C., and the pre-oxidation time is 2 hours.

[0015] It is further defined that in step S3, carbonization is completed at a temperature of 650°C-900°C in a nitrogen protective atmosphere; and then the temperature is cooled at a rate of 5°C / min-10°C / min.

[0016] Using the Cu2O / FeO x Cu2O / FeO prepared by the preparation method of @CNFs heterojunction nanozyme x @CNFs heterojunction nanozymes.

[0017] Further definition, Cu2O / FeO x Cu2O / FeO@CNFs heterojunction nanozymes xIt is a pn heterojunction.

[0018] It is further defined that the Cu2O / FeO x @CNFs heterojunction nanozymes have good broad-spectrum bactericidal properties and the ability to degrade pollutants or microplastics.

[0019] As described in Cu2O / FeO x @Application of CNFs heterojunction nanozymes in food safety.

[0020] The technical effects produced by the present invention are as follows:

[0021] 1. Cu2O / FeO prepared by the present invention x Cu2O / FeO in @CNFs heterojunction nanozymes x It is a pn heterojunction; through Cu2O and FeO x The built-in electric field at the interface accelerates the reduction rate of surface Fe(III) generated in the Fenton reaction, exhibiting efficient peroxidase-like activity and Fenton reaction efficiency.

[0022] 2. Cu2O / FeO prepared by the present invention x Cu2O / FeO in @CNFs heterojunction nanozymes x Constrained by CNFs, it is not prone to structural evolution or material diffusion and has high stability.

[0023] 3. Cu2O / FeO prepared by the present invention x @CNFs heterojunction nanozymes showed good antibacterial effects against both Gram-positive and Gram-negative bacteria.

[0024] 4. Cu2O / FeO prepared by the present invention x @CNFs heterojunction nanozymes show good catalytic degradation effect on the common pollutant Rhodamine B (RhB), and can have a preliminary degradation effect on microplastics.

[0025] 5. Cu2O / FeO prepared by the present invention x @CNFs heterojunction nanozymes have strong magnetism, exhibit good magnetic separation properties and recyclability, are suitable for multiple recycling, and reduce processing costs.

[0026] 6. Cu2O / FeO of the present invention x @The preparation method of CNFs heterojunction nanozymes is safe and economical; it is used in food safety and provides an innovative, efficient and environmentally friendly technical approach for the food processing field. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1Cu2O / FeO x @CNFs physical properties results; a is Cu2O / FeO x @SEM image of CNFs; b is a high-resolution transmission electron microscope (HR-TEM) image; c is an X-ray photoelectron spectroscopy (XPS) image; d is an X-ray photoelectron spectroscopy Fe 2p spectrum; e is an X-ray photoelectron spectroscopy Cu 2p spectrum; f is an X-ray diffraction spectrum (XRD) image;

[0028] Figure 2 Medium Cu2O / FeO x @CNFs peroxidase activity results; a is Cu2O / FeO x @TMB (3,3',5,5'-tetramethylbenzidine) color development under the action of CNFs peroxidase activity; b is Cu2O / FeO x @ABTS (2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt) color development under the action of CNFs peroxidase activity; c is Cu2O / FeO x @ OPD (o-phenylene phosphate disodium) color development diagram under the action of CNFs peroxidase activity;

[0029] Figure 3 Cu2O / FeO x @The peroxidase-like enzyme kinetic curve of CNFs; (a) is the enzyme kinetic curve corresponding to TMB; (b) is the enzyme kinetic curve corresponding to H2O2;

[0030] Figure 4 Cu2O / FeO x @Bacterial plate coating effect of CNFs sterilization;

[0031] Figure 5 Cu2O / FeO x @CNFs bactericidal effect; a is Cu2O / FeO x @The relationship between the bactericidal effect of CNFs on Escherichia coli and time, b is Cu2O / FeO x @The relationship between the bactericidal effect of CNFs on Staphylococcus aureus and time, c is Cu2O / FeO x @CNFs sterilization rate of Escherichia coli and its relationship with concentration, d is Cu2O / FeO x @The relationship between the sterilization rate of CNFs against Staphylococcus aureus and its concentration;

[0032] Figure 6 Cu2O / FeO x @CNFs degradation effect on organic pollutants; a is Cu2O / FeOx @CNFs degraded Rhodamine B (RhB) color change; b is Cu2O / FeO x @The absorbance curve of CNFs degrading RhB; c is the absorbance curve of different materials degrading RhB;

[0033] Figure 7 SEM images of microplastics after treatment with different materials;

[0034] Figure 8 Cu2O / FeO x Fourier infrared spectra of microplastics after @CNFs treatment;

[0035] Fig. 9 Cu2O / FeO x @Changes in particle size of microplastics after CNFs treatment;

[0036] Fig.10 Cu2O / FeO x @Diagram of the magnet recovery effect of CNFs heterojunction nanozymes. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0038] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0039] Technologies, methods, and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.

[0040] The disclosed contents of the prior art documents cited in the present specification are incorporated into the present invention by reference in their entirety and are therefore part of the disclosure of the present invention.

[0041] The present invention provides a Cu2O / FeO x The preparation method of @CNFs heterojunction nanozyme comprises the following steps:

[0042] S1. Decolorizing and washing bacterial cellulose BC to complete pretreatment.

[0043] In step S1, decolorization is carried out in an alkaline environment, the decolorization temperature is 80° C. to 100° C., and the decolorization time is 1.5 h to 3 h; and washing is carried out with water.

[0044] Preferably, NaOH solution is used for decolorization, the concentration of NaOH solution is 0.01 mol / L to 0.02 mol / L, and the amount used is 700 mL to 850 mL.

[0045] S2. The pretreated BC is immersed in a mixed solution containing Fe(II) and Cu(II), stirred evenly, and then rinsed to obtain BC-Cu(II) / Fe(II).

[0046] In step S2 of the present invention, the mass volume ratio of BC and the mixed solution is (4mg-6mg):0.5L.

[0047] Preferably, the concentration of Fe(II) is 10 mmol / L to 30 mmol / L, the concentration of Cu(II) is 10 mmol / L to 25 mmol / L, and the ratio of the concentration of Fe(II) to the concentration of Cu(II) is (1 to 3):1.

[0048] In step S2 of the present invention, the stirring time is 6 h to 24 h.

[0049] S3, the BC-Cu(II) / Fe(II) in step S2 is freeze-dried, pre-oxidized, carbonized, and cooled to obtain Cu2O / FeO x @CNFs heterojunction nanozymes.

[0050] In step S3 of the present invention, the pre-oxidation temperature is 150° C. to 200° C., and the pre-oxidation time is 2 hours.

[0051] In step S3 of the present invention, carbonization is completed at a temperature of 650° C. to 900° C. in a nitrogen protective atmosphere; and then the temperature is reduced and cooled at a rate of 5° C. / min to 10° C. / min.

[0052] The Cu2O / FeO prepared by the above preparation method of the present invention x @CNFs heterojunction nanozyme, whose structure is pn heterojunction.

[0053] The Cu2O / FeO prepared by the above preparation method of the present invention x @CNFs heterojunction nanozymes have good broad-spectrum bactericidal properties and the ability to degrade pollutants or microplastics, and can be used in food safety.

[0054] The following are several examples of the method for preparing Cu2O / FeO x @CNFs heterojunction nanozyme method is described in detail.

[0055] It should be noted that, unless otherwise specified, the drugs and reagents used in the following examples are all commercially available products, and the operating methods used are all conventional operations in the art.

[0056] In the following examples, bacterial cellulose is denoted as BC.

[0057] Example 1

[0058] This embodiment provides a Cu2O / FeO x The preparation method of @CNFs heterojunction nanozyme comprises the following steps:

[0059] S1. Take 5.0 mg BC and dissolve it in 750 ml of 0.01 mol / L NaOH solution, decolorize it at 90°C for 2 h, then rinse it with ultrapure water to a neutral pH value, and then remove the residual water by freeze drying to complete the BC pretreatment.

[0060] S2. Immerse the BC dried in step S1 in a mixed solution containing 30 mmol / L FeSO4·4H2O and 15 mmol / L CuSO4·5H2O, the volume of the mixed solution is 0.5 L, stir at a stirring speed of 200 r / min for 10 h, and then rinse with ultrapure water 5 times to remove excess metal ions to obtain BC-Cu(II) / Fe(II).

[0061] S3, further freeze-drying to remove moisture from BC-Cu(II) / Fe(II), and pre-oxidizing at 180°C for 2h; after pre-oxidation, heating to 750°C for carbonization under nitrogen protection for 2h; cooling to room temperature at a rate of 7°C / min to form Cu2O / FeO x @CNFs heterojunction nanozymes.

[0062] Example 2

[0063] This embodiment provides a Cu2O / FeO x The preparation method of @CNFs heterojunction nanozyme comprises the following steps:

[0064] S1. Take 4.5 mg BC and dissolve it in 800 ml of 0.015 mol / L NaOH solution, decolorize it at 85°C for 1.5 h, then rinse it with ultrapure water to neutral pH, and then remove the residual water by freeze drying to complete the BC pretreatment.

[0065] S2. The dried BC was immersed in a mixed solution containing 25 mmol / L FeSO4·4H2O and 25 mmol / L CuSO4·5H2O. The volume of the mixed solution was 0.5 L. It was stirred at a stirring speed of 180 r / min for 8 h, and then rinsed with ultrapure water 5 times to remove excess metal ions to obtain BC-Cu(II) / Fe(II).

[0066] S3, further freeze-drying to remove moisture from BC-Cu(II) / Fe(II), and pre-oxidizing at 150°C for 1 hour; after pre-oxidation, heating to 900°C for carbonization under nitrogen protection and maintaining for 3 hours; cooling to room temperature at a rate of 5°C / min to form Cu2O / FeO x @CNFs heterojunction nanozymes.

[0067] Example 3

[0068] This embodiment provides a Cu2O / FeO x The preparation method of @CNFs heterojunction nanozyme comprises the following steps:

[0069] S1. Take 6.0 mg BC and dissolve it in 700 ml of 0.02 mol / L NaOH solution, decolorize it at 95°C for 3 h, then rinse it with ultrapure water to neutral pH, and then remove the residual water by freeze drying to complete the BC pretreatment.

[0070] S2. The dried BC was immersed in a mixed solution containing 30mmol / L FeSO4·4H2O and 10mmol / L CuSO4·5H2O. The volume of the mixed solution was 0.5L. It was stirred at a stirring speed of 220r / min for 12h, and then rinsed with ultrapure water 5 times to remove excess metal ions to obtain BC-Cu(II) / Fe(II).

[0071] S3, further freeze-drying to remove moisture from BC-Cu(II) / Fe(II), and pre-oxidizing at 200℃ for 3h; after pre-oxidation, heating to 650℃ for carbonization under nitrogen protection for 4h; cooling to room temperature at a rate of 10℃ / min to form Cu2O / FeO x @CNFs heterojunction nanozymes.

[0072] Example 4

[0073] This embodiment provides a Cu2O / FeO x The preparation method of @CNFs heterojunction nanozyme comprises the following steps:

[0074] S1. Take 5.5 mg of BC and dissolve it in 850 ml of 0.01 mol / L NaOH solution, decolorize it at 82°C for 2.5 h, then rinse it with ultrapure water to neutral pH, and then remove the residual water by freeze drying to complete the BC pretreatment.

[0075] S2. Immerse the BC dried in step S1 in a mixed solution containing 20 mmol / L FeSO4·4H2O and 20 mmol / L CuSO4·5H2O, the volume of the mixed solution is 0.5 L, stir at a stirring speed of 250 r / min for 9 hours, and then rinse with ultrapure water 5 times to remove excess metal ions to obtain BC-Cu(II) / Fe(II).

[0076] S3, further freeze-drying to remove moisture from BC-Cu(II) / Fe(II), and pre-oxidizing at 180°C for 2h; after pre-oxidation, heating to 800°C for carbonization under nitrogen protection and maintaining for 2h; cooling to room temperature at a rate of 5°C / min to form Cu2O / FeO x @CNFs heterojunction nanozymes.

[0077] Further, the Cu2O / FeO prepared in the above example was tested by the following test: x @CNFs heterojunction nanozyme performance was verified, thereby demonstrating the advantages of the technology adopted in the present invention.

[0078] In order to prove that Cu2O / FeO x @The performance of CNFs heterojunction nanozymes, the following comparative example is set up.

[0079] Comparative Example 1

[0080] This comparative example provides a FeO x The preparation method of @CNFs nanozyme comprises the following steps:

[0081] S1. Take 5.5 mg of BC and dissolve it in 850 ml of 0.01 mol / L NaOH solution, decolorize it at 82°C for 2.5 h, then rinse it with ultrapure water to neutral pH, and then remove the residual water by freeze drying to complete the BC pretreatment.

[0082] S2. Immerse the BC dried in step S1 in a mixed solution containing 20 mmol / L FeSO4·4H2O, stir at a stirring speed of 250 r / min for 9 h, and then rinse with ultrapure water 5 times to remove excess metal ions to obtain BC-Fe(II).

[0083] S3, further remove the moisture in BC-Fe(II) by freeze drying, and pre-oxidize at 180°C for 2h; after the pre-oxidation, heat to 800°C under nitrogen protection for carbonization treatment, and keep it for 2h; cool to room temperature at a cooling rate of 5°C / min to form FeO x @CNFs nanozymes.

[0084] Comparative Example 2

[0085] This embodiment provides a method for preparing Cu2O@CNFs nanozyme, comprising the following steps:

[0086] S1. Take 5.5 mg of BC and dissolve it in 850 ml of 0.01 mol / L NaOH solution, decolorize it at 82°C for 2.5 h, then rinse it with ultrapure water to neutral pH, and then remove the residual water by freeze drying to complete the BC pretreatment.

[0087] S2. Immerse the BC dried in step S1 in a mixed solution containing 20 mmol / L CuSO4·5H2O, stir at a stirring speed of 250 r / min for 9 hours, and then rinse with ultrapure water 5 times to remove excess metal ions to obtain BC-Cu(II).

[0088] S3. Further remove moisture from BC-Cu(II) by freeze drying and pre-oxidize at 180°C for 2 h. After pre-oxidation, heat to 800°C for carbonization under nitrogen protection and maintain for 2 h. Then cool to room temperature at a cooling rate of 5°C / min to form Cu2O@CNFs nanozyme.

[0089] Test 1

[0090] Sample: Cu2O / FeO obtained in Example 4 x @CNFs heterojunction nanozymes.

[0091] Test method: Cu2O / FeO x The physical properties of @CNFs heterojunction nanozymes were characterized. Figure 1 shown.

[0092] See also Figure 1 , a is Cu2O / FeO x @SEM image of CNFs heterojunction nanozyme, showing that the synthesized material presents a fibrous morphology; b is Cu2O / FeO x HR-TEM image of @CNFs heterojunction, revealing the Cu2O and FeO x Different lattice structures formed on the CNFs substrate, where the lattice spacing of Cu2O is measured to be 0.240nm, which is consistent with the (111) crystal plane spacing of Cu2O; x The lattice spacing of Cu2O and FeO is 0.257nm, which is consistent with the (101) crystal plane spacing of FeO. xThe characteristic defects caused by lattice mismatch were observed at the interface of the composite material. The chemical states of different elements in the composite material were deeply explored by X-ray photoelectron spectroscopy (XPS) analysis, and the full-spectrum XPS spectrum of the material (c) and high-resolution spectra of Cu and Fe elements (d and e) were obtained, showing the composition of the composite material, indicating that Cu in the prepared material will transfer electrons to Fe, promoting the reduction of Fe element; f is the XRD spectrum, indicating that Cu2O and FeO x It has a good lattice structure and is successfully loaded on CNFs.

[0093] Test 2

[0094] Sample: Cu2O / FeO obtained in Example 4 x @CNFs heterojunction nanozymes.

[0095] Test method: The peroxidase-like activity of the sample was evaluated by catalytic oxidation of TMB, ABTS and OPD. Under the action of different materials and H2O2, the color depth of TMB, ABTS and OPD was positively correlated with the peroxidase-like activity, indicating that the material has high catalytic activity.

[0096] The color development results are as follows Figure 2 As shown, ① is H2O2, ② is FeO x @CNFs+H2O2, ③ is Cu2O@CNFs+H2O2, ④ is Cu2O / FeO x @CNFs+H2O2.

[0097] See also Figure 2 Whether TMB, ABTS or OPD is used as substrate, Cu2O / FeO x The colors of the @CNFs+H2O2 group are the darkest, followed by Cu2O@CNFs, FeO x @CNFs, showing the Cu2O / FeO x @CNFs have the highest peroxidase-like activity.

[0098] In this experiment, TMB was used as the chromogenic substrate to x @CNFs peroxidase-like activity was tested for enzyme catalytic kinetics. Figure 3 shown.

[0099] See also Figure 3 The Cu2O / FeO x The affinity and maximum reaction rate of @CNFs for TMB and H2O2 are better than those of FeO x @CNFs and Cu2O@CNFs.

[0100] Test 3

[0101] Sample: FeO of Comparative Example 1 x @CNFs nanozyme, Cu2O@CNFs nanozyme of comparative example 2, Cu2O / FeO x @CNFs nanozymes.

[0102] Test method: FeO x @CNFs, Cu2O@CNFs and Cu2O / FeO x @CNFs were mixed with ultrapure water at a mass ratio of 1:20 to obtain FeO x @CNFs solution, Cu2O@CNFs solution and Cu2O / FeO x @CNFs solution.

[0103] The above three solutions were mixed with 50 μL and 500 mmol / L H2O2 solutions and target microorganisms (Gram-positive bacteria and Gram-negative bacteria) for incubation experiments to evaluate the bactericidal performance of the nanozymes.

[0104] In the test, Gram-positive bacteria were represented by Staphylococcus aureus (S. aureus), and Gram-negative bacteria were represented by Escherichia coli (E. coli).

[0105] (1) The bactericidal effects of the three nanozymes were tested by the plate coating method. The number of colony forming units (CFU) on the plate decreased, indicating that the materials had bactericidal efficacy. The results are as follows Figure 4 shown.

[0106] See also Figure 4 The bactericidal effects of each sample on Staphylococcus aureus and Escherichia coli show that Cu2O / FeO x @CNFs had the best bactericidal effect, followed by Cu2O@CNFs and FeO x @CNFs, showing the Cu2O / FeO x @CNFs have good broad-spectrum bactericidal properties.

[0107] (2) The sterilization rate calculation method was used to further evaluate the relationship between sterilization effect and time, and sterilization effect and concentration for each material. The results are as follows: Figure 5 shown.

[0108] See also Figure 5 a and 5b, time-dependent sterilization curves show that Cu2O / FeO x @CNFs nanozymes showed better performance than Cu2O@CNFs and FeO in a shorter time. x@CNFs have higher bactericidal efficiency and can completely kill Escherichia coli and Staphylococcus aureus within 0.5 hours, showing a significant bactericidal effect. x The bactericidal efficiency of @CNFs nanozymes was slightly lower than that of Cu2O@CNFs in the initial stage, and its bactericidal efficiency gradually decreased with the extension of mixing time, indicating that FeO x @CNFs Fenton reaction is limited, while Cu2O / FeO x @ The sterilization rate of CNFs did not decrease significantly with time; see Figure 5 c and 5d, from the bactericidal concentration dependence curve, it can be found that with the increase of concentration, Cu2O / FeO x @CNFs have a lower minimum bactericidal concentration (MBC).

[0109] The above tests show that Cu2O / FeO x @CNFs heterojunction nanozymes showed good antibacterial effects against both Gram-positive and Gram-negative bacteria.

[0110] Test 4

[0111] Sample: FeO of Comparative Example 1 x @CNFs nanozyme, Cu2O@CNFs nanozyme of comparative example 2, Cu2O / FeO x @CNFs nanozymes.

[0112] Test method: FeO x @CNFs, Cu2O@CNFs and Cu2O / FeO x @CNFs were mixed with ultrapure water at a mass ratio of 1:20 to obtain FeO x @CNFs solution, Cu2O@CNFs solution and Cu2O / FeO x @CNFs solution.

[0113] The above three solutions were mixed with 50 μL and 500 mmol / L H2O2 solutions and organic pollutants (Rhodamine B (RhB)) for incubation experiments to clarify the pollutant degradation performance of the nanozyme.

[0114] In the experiment, RhB was used as a pollutant for degradation experiments, and the degradation efficiency of the three nanozymes on pollutants was evaluated. The results are as follows: Figure 6 shown.

[0115] Experimental process: FeO x @CNFs, Cu2O@CNFs and Cu2O / FeO x@CNFs and H2O2 were mixed in an acetic acid-sodium acetate (NaAc-HAc) buffer solution (pH = 4.0) to form a reaction system. 2 mL of RhB solution was added to the reaction system with an initial concentration of 500 mg / L. The reaction was allowed to proceed for 24 hours at room temperature, and the degradation effect of RhB was detected by UV-visible spectroscopy.

[0116] See also Figure 6 a, Cu2O / FeO x @CNFs-treated RhB solution achieved significant decolorization effect within 48 h; see Figure 6 b, absorbance measurements confirm effective degradation of pollutants, see Figure 6 c, After 48h treatment with different materials, Cu2O / FeO x @CNFs has the most obvious decrease in absorbance at the maximum absorption peak. x @CNFs have good degradation effect on pollutants.

[0117] Test 5

[0118] Sample: Cu2O / FeO of Example 4 x @CNFs nanozymes.

[0119] Test method: Using Cu2O / FeO x @CNFs degrade microplastics. The degradation test refers to the degradation process of organic pollutants in Test 4. The degradation effect is as follows: Figure 7 , Figure 8 and Fig. 9 shown.

[0120] See also Figure 7 , after 24 hours of treatment, the morphology of microplastics changed significantly; see Figure 8 , Cu2O / FeO x Fourier infrared spectra of the mixture of @CNFs and microplastics show that Cu2O / FeO x @CNFs adsorption of microplastics; see Fig. 9 The particle size of microplastics was measured at different treatment times and it was found that the particle size of microplastics decreased, which verified the Cu2O / FeO x @The degradation effect of CNFs on microplastics.

[0121] Test 6

[0122] Sample: Cu2O / FeO of Example 4 x @CNFs nanozymes.

[0123] Test method: Cu2O / FeO x@CNFs were used in the magnet adsorption recovery experiment. The adsorption test process was to convert Cu2O / FeO x @CNFs were fully dispersed in ultrapure water to form a uniform suspension. The nanomaterials in the suspension were adsorbed by a magnet. After 10 minutes, Cu2O / FeO x @CNFs are adsorbed by magnets. The results are as follows Fig.10 shown.

[0124] See also Fig.10 , indicating that Cu2O / FeO x @CNFs nanozymes have strong magnetism and show good recyclability. The feasibility of magnetic recycling provides a scientific basis for its recycling and environmental friendliness.

[0125] The present invention aims to develop a Cu2O / FeO x @CNFs heterojunction nanozymes, through their unique pn-type heterostructure design, achieve a significant improvement in the catalytic efficiency of the Fenton reaction; the nanozymes use a built-in electric field to accelerate the electron transfer process of Fe(II) / Fe(III), effectively overcoming the inefficiency of traditional Fenton reaction catalysts and showing excellent performance in sterilization and pollutant degradation. In addition, heterojunction nanozymes have magnetic properties and can be easily and efficiently recycled by magnets, which not only reduces the risk of secondary pollution, but also greatly reduces the economic cost and environmental burden of long-term applications.

[0126] The specific embodiments described above are only used to explain the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention / invention.

Claims

1. A Cu2O / FeO x @CNFs heterojunction nanozyme preparation method, characterized in that, The following steps are involved: S1, decolorizing and washing bacterial cellulose BC to complete pretreatment; S2. The pretreated BC is immersed in a mixed solution containing Fe(II) and Cu(II), stirred evenly, and then rinsed to obtain BC-Cu(II) / Fe(II); the mass volume ratio of the BC and the mixed solution is (4mg~6mg):0.5L; the concentration of Fe(II) is 10mmol / L~30mmol / L, and the concentration of Cu(II) is 10mmol / L~25mmol / L. S3, the BC-Cu(II) / Fe(II) in step S2 is freeze-dried, pre-oxidized, carbonized, and cooled to obtain Cu2O / FeO x @CNFs heterojunction nanozymes.

2. Cu2O / FeO according to claim 1 x @CNFs heterojunction nanozyme preparation method, characterized in that, In the step S1, decolorization is carried out in an alkaline environment, the decolorization temperature is 80° C. to 100° C., and the decolorization time is 1.5 h to 3 h; and washing is carried out with water.

3. Cu2O / FeO according to claim 1 x @CNFs heterojunction nanozyme preparation method, characterized in that, In step S2, the concentration ratio of Fe(II) to Cu(II) is (1-3):

1.

4. Cu2O / FeO according to claim 3 x @CNFs heterojunction nanozyme preparation method, characterized in that, In step S2, the stirring time is 6 h to 24 h.

5. Cu2O / FeO according to claim 1 x @CNFs heterojunction nanozyme preparation method, characterized in that, In step S3, the pre-oxidation temperature is 150° C. to 200° C., and the pre-oxidation time is 2 hours.

6. Cu2O / FeO according to claim 5 x @CNFs heterojunction nanozyme preparation method, characterized in that, In the step S3, carbonization is completed at a temperature of 650° C. to 900° C. in a nitrogen protective atmosphere; and then the temperature is reduced and cooled at a rate of 5° C. / min to 10° C. / min.

7. Utilize the Cu2O / FeO of claim 1 x Cu2O / FeO prepared by the preparation method of @CNFs heterojunction nanozyme x @CNFs heterojunction nanozymes.

8. Cu2O / FeO according to claim 7 x @CNFs heterojunction nanozyme, characterized by Cu2O / FeO x The structure is a pn heterojunction.

9. Cu2O / FeO according to claim 7 x @CNFs heterojunction nanozyme, characterized by The Cu2O / FeO x @CNFs heterojunction nanozymes have good broad-spectrum bactericidal properties and the ability to degrade pollutants or microplastics.

10. Cu2O / FeO as claimed in claim 7 x @Application of CNFs heterojunction nanozymes in food safety.